Role of ITO nanoparticles embedded into electrospun ITO nanofibers. (31st October 2017) - Yoon, Sangcheol; Kim, Hyebin; Cha, Seung-Jae; Shin, Eun-Sol; Noh, Yong-Young; Hong, Sung-Jei; Park, Byoungchoo; Hwang, Inchan
Abstract: Both crystallization and molecular density are significant to achieve high electrical conductivity of transparent electrodes. Herein, we investigated the embedding effects of indium tin oxide (ITO) nanoparticles (NPs) into ITO nanofibers (NFs) synthesized by utilizing an electrospinning technique from ITO precursor solutions. We found that the ITO NPs might act as nucleation seeds that initiate crystallization of ITO, evidenced by flake-like morphologies which cannot be observed without ITO NPs. XRD measurements reveal that the ITO is crystalline with a higher degree and the size of ITO crystallites increases in the presence of ITO NPs embedded into NFs. Embedding ITO NPs leads to the formation of short fibers, but there is still large space between fibers as they are vertically stacked in the films, resulting in low electrical conductivity. Interestingly, a high ratio of ITO NPs enhances the electrical conductivity, as compared to a low ratio, which we attribute to the high fiber density on substrates due to the formation of shorter ITO NFs. Our results highlight that the ITO NPs influence not only the ITO crystallization but also the lengths of NFs. High electrical conductivity of NF films can be obtained by a high degree of crystallization and the optimum NF length that reduces spaces between NFs in the films.